Analysing the inconsistent recognition of Indigenous rights in early childhood policy documents from the Australian Government’s "Closing the Gap" strategy between 2008-2018 - George, Emma; Mackean, Tamara; Fisher, Matt; Baum, Fran (The International Indigenous Policy Journal, 2023)
We analysed Australian government strategic policy documents related to the "Closing the Gap" (CTG) strategy in early childhood circa 2008-2018 to explore the extent to which Indigenous rights are named and recognised in written policy. Our analysis of the policies was informed by Bacchi’s What’s the Problem approach and showed inconsistency in the recognition of Indigenous rights. These rights are sometimes undermined and ignored, sometimes implied and sometimes named and recognised. Silences within the CTG strategy are discussed and reveal the ongoing nature of colonisation and deficit framing of Aboriginal and Torres Strait Islander people and communities. Findings from this research are relevant for the current era of the "Closing the Gap" strategy.